2022
DOI: 10.1080/21655979.2022.2073655
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-135b-5p regulates trophoblast cell function by targeting phosphoinositide-3-kinase regulatory subunit 2 in preeclampsia

Abstract: The level of miR‑135b-5p is lower in patients with preeclampsia (PE) superimposed on chronic hypertension than in healthy controls. However, the function of miR‑135b-5p in PE progression remains unknown. In the present study, we investigated the role of miR‑135b-5p in PE development and its possible mechanism for the first time. HTR8/SVneo cells (trophoblast cell line) were exposed to hypoxia/reoxygenation (H/R) to mimic PE in vitro . Hypoxia-inducible factor-1α (HIF-1α), forkhead box O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The translocation of AmEVs in the placenta and the remission of PE symptoms in AmEVs‐pretreated mice prompted us to investigate the potential mechanism of AmEVs in human cell line. Accordingly, we employed the human first‐trimester trophoblast HTR‐8/SVneo cell line to establish a hypoxia/reoxygenation (H/R) model to mimic the state of PE trophoblast based on previous studies (Zhang & Zhang, 2022 ). The cell proliferation rate was significantly higher in groups pretreated with 10 or 20 μg/mL AmEVs than in the H/R group (Figure 7a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The translocation of AmEVs in the placenta and the remission of PE symptoms in AmEVs‐pretreated mice prompted us to investigate the potential mechanism of AmEVs in human cell line. Accordingly, we employed the human first‐trimester trophoblast HTR‐8/SVneo cell line to establish a hypoxia/reoxygenation (H/R) model to mimic the state of PE trophoblast based on previous studies (Zhang & Zhang, 2022 ). The cell proliferation rate was significantly higher in groups pretreated with 10 or 20 μg/mL AmEVs than in the H/R group (Figure 7a ).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were grown in a humidified incubator at 37°C with 5% CO 2 . To establish a trophoblast cell model of PE, the HTR‐8/SVneo cells were cultured at 37°C for 8 h under hypoxic conditions (2% O 2 ), followed by 16 h of reoxygenation (H/R) under 5% CO 2 /air; the cells were grown under 5% CO 2 /air at 37°C and served as controls (Zhang & Zhang, 2022 ). To test the impact of AmEVs, cells were pretreated with different concentrations (1, 10, 20 or 50 μg/mL) of AmEVs in a fresh culture medium for 24 h, and then subjected to 8 h of hypoxia and 16 h of reoxygenation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, as a NO synthase inhibitor, L-NAME gives rise to oxidative stress injury in the placenta, which has been demonstrated in the present study. In addition, many studies have been carried out on trophoblast cell models to elucidate the origin of oxidative stress, specifically H/R-treated HTR8/SVneo cells (Gu et al, 2022;Zhang and Zhang, 2022). Several studies suggested that placental lipid peroxides increased and placental antioxidant protective effects decreased in PE (Vaka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA and mRNA expression levels were normalized against U6 and GAPDH, respectively. 31,[41][42][43][44] Reaction conditions for qRT-PCR were as follows: 95°C 30s, 55°C 30s, and 72°C 90s, for a total of 40 cycles. All samples were repeated three times, and the primers used in this study are listed in Table 1.…”
Section: Reverse Transcription-quantitative (Rt-qpcr)mentioning
confidence: 99%